Production and characterization of rhamnolipid biosurfactant from thermophilic Geobacillus stearothermophilus bacterium isolated from Uhud mountain - Albasri, Hibah M.; Almohammadi, Asmaa A.; Alhhazmi, Areej; Bukhari, Duaa A.; Waznah, Moayad S.; Mawad, Asmaa M. M. (Frontiers in Microbiology, 2024)
Biosurfactants have been given considerable attention as they are potential candidates for several biotechnological applications. In this study, a promising thermophilic biosurfactant-producing HA-2, was isolated from volcanic and arid region Uhud mountain, Madinah, SA. It was identified using 16S rRNA gene sequence analysis as Geobacilluss stearothermophilus strain OR911984. It could utilize waste sunflower frying oil (WSFF) oil as a low-cost carbon source. The biosurfactant production ability was screened using different methods including drop collapse test, oil spreading test, hemolytic activity test, CTAB test and emulsification index. It showed high emulsification activity (52±0.0%) and positive results towards other biosurfactant screening tests. FTIR spectra indicated the presence of hydrophobic chain that comprises of lipid, sugar nature and hydrophilic glycolipid part. The ability of rhamnolipid production by the tested strain was confirmed by the PCR of rhlAB. The affinity of thermophilic HA-2 to hydrophobic substrates was also investigated and it showed high cell adhesion to hexane with cell surface hydrophobicity (41.2%). Optimization of biosurfactant production was conducted and the results showed that the optimal conditions were potato peel as a carbon source with emulsification activity 68.8%, yeast extract as a nitrogen source (60%), pH of 9 (56.6%) and at 50 ℃ (72%). The kinetics showed that optimum biosurfactant production (572.4 mg/L) was recorded at five days of incubation. The produced rhamnolipid biosurfactant showed high antimicrobial activity against some human and plant pathogenic bacterial and fungal isolates, and high antioxidant activity (90.4%). In addition, it enhanced wheat (Triticum aestivum) growth with the greatest stimulation obtained with concentration 5%. Therefore, thermophilic G. stearothermophilus is a promising rhamnolipid biosurfactant producer, which could utilize many organic wastes. The produced biosurfactant would be applied as a promising emulsifier, antimicrobial, antioxidant and plant growth promoter candidate.